Psychiatric Characteristics Across Individuals With PTEN Mutations - Steele, Morgan; Uljarević, Mirko; Rached, Gaëlle; Frazier, Thomas W.; Phillips, Jennifer M.; Libove, Robin A.; Busch, Robyn M.; Klaas, Patricia; Martinez-Agosto, Julian A.; Srivastava, Siddharth; Eng, Charis; Sahin, Mustafa; et al. (Frontiers in Psychiatry, 2021)
Germline heterozygous PTEN mutations have been associated with high prevalence of autism spectrum disorder (ASD) and elevated rates and severity of broadly defined behavioral problems. However, limited progress has been made towards understanding whether PTEN mutation is associated with specific psychiatric co-morbidity profiles when compared to idiopathic ASD. The current study aimed to utilize a cross-measure approach to compare concurrent psychiatric characteristics across children and adolescents with PTEN mutation with (PTEN-ASD; n=38) and without ASD (PTEN-No ASD; n=23), and ASD with macrocephaly but no PTEN mutation (macro-ASD; n=25) using the Child Behavior Checklist (CBCL) and the Aberrant Behavior Checklist (ABC). There were significant group effects for the CBCL Internalizing and Externalizing broad symptom score, the majority of specific CBCL syndrome scores, and all ABC subscale scores. Post-hoc comparisons revealed greater behavioral symptoms in the ASD groups (PTEN-ASD and macro-ASD) compared to the PTEN-no ASD group on nearly all subtest scores examined. There were no statistically significant differences between the PTEN-ASD and macro-ASD groups; however, there was a trend for the macro-ASD group showing higher levels of aggressive behaviors. Our findings provide evidence of specific behavior profiles across PTEN-No ASD, PTEN-ASD, and macro-ASD groups and highlight the importance of early identification of behavioral vulnerabilities in individuals with PTEN mutations in order to provide access to appropriate evidence-based interventions.